Structured health education and risk of alcohol-related harm among youth in Kiambu, Kenya: a quasi-experimental study - Mukui, Antony K.; Oyore, John P.; Gitahi, Mary M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Alcohol remains a major contributor to mortality and increased disability adjusted life years (DALYs) among the youth. In Kenya, where youth alcohol consumption affects 13% of 15–24 year old and reaches 28.9% in Kiambu County, structured health education interventions remain underexplored as a prevention strategy, and this informs the current study title. Methods: Fourteen trained community health promoters delivered 12 monthly one-hour structured sessions over 12 months, supported by educational materials and peer learning components. Using the World Health Organisation alcohol use disorders identification test (WHO AUDIT) tool, 356 participants were randomly allocated per arm, following power calculations to detect an 11% risk reduction with 80% power. AUDIT scores categorized participants as low-risk, risky-hazardous, harmful, or high-risk, while the questionnaire established sociodemographic characteristics. Qualitative data were analyzed thematically. Kenyatta University's ethics committee granted study approval. Results: Comparing pre- and post-study results, the mean risk in the intervention group dropped from 14.4 (risky-hazardous) to 4.8 (low risk), while the control group increased from 11.4 (risky-hazardous) to 18 (harmful). Youths with higher odds of risk were male, aged 20-24 years, uneducated, unemployed, not living with parents, widowed, separated, divorced, and residing in suburban areas, particularly in Muguga ward. The study reported a DiD estimate of -16.197 and a Cohen’s d of -1.882, indicating that participants in the intervention group scored 16 points lower on the AUDIT scale. FGDs and KIIs revealed limited awareness and access to screening services, and intervention youths reported decreased alcohol consumption. Conclusion: The intervention raised awareness of alcohol-related harm and reduced the risk of harm.